KASUS KOMPLEKS OEDIPUS (OEDIPUS COMPEX) DALAM CERPEN MENGAWINI IBU KARYA KHRISNA PABICHARA: KAJIAN PRIKOANALISIS - Syam, Essy (Jurnal Ilmu Budaya, 2012)
Freud's idea about Oedipus complex refers to emotion and feeling of desire of a boy for his mother in which he desires to posses his mother sexually and kill his father due to his jealousy and anger to his father. For him, his father is his rival for his mother's attention and affection. That's why his wish is to posses his mother, replace his faher. This phenomena is analyzed in a short story entitles "Mengawini Ibu" written by Khrisna Pabichara highlighting the case of Oedipal condition.